2010
DOI: 10.1186/1471-2350-11-48
|View full text |Cite
|
Sign up to set email alerts
|

MFN2point mutations occur in 3.4% of Charcot-Marie-Tooth families. An investigation of 232 Norwegian CMT families

Abstract: BackgroundPoint mutations in the mitofusin 2 (MFN2) gene has been identified exclusively in Charcot-Marie-Tooth type 2 (CMT2), and in a single family with intermediate CMT. MFN2 point mutations are probably the most common cause of CMT2.MethodsTwo-hundred and thirty-two consecutive unselected and unrelated CMT families with available DNA from all regions in Norway were included. We screened for point mutations in the MFN2 gene.ResultsWe identified four known and three novel point mutations in 8 unrelated CMT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…(Arg468His)C5[2931]8CMT1 MFN2 NM_014874.3c.1403G > Ap. (Arg468His)C5[2931]9CMT1 MFN2 NM_014874.3c.2119A > Gp. (Arg707Trp)C5[31]10CMT2 PMP22 NM_000304.2c.448G > Cp.…”
Section: Resultsmentioning
confidence: 99%
“…(Arg468His)C5[2931]8CMT1 MFN2 NM_014874.3c.1403G > Ap. (Arg468His)C5[2931]9CMT1 MFN2 NM_014874.3c.2119A > Gp. (Arg707Trp)C5[31]10CMT2 PMP22 NM_000304.2c.448G > Cp.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studies of the exact functional mechanism of Mfn2, which has been confirmed to exert a potential apoptotic effect via the mitochondrial apoptotic pathway (5), are essential. In the present study, we investigated Mfn2, which has been widely studied in Charcot-Marie-Tooth disease (16). Mfn2 is known to be correlated with antitumor activity in a number of malignancies (5-7); however, its effect in breast cancers has not been previously reported.…”
Section: Mfn2 Suppresses Cell Cycle Progression Via the Pi3k/akt Signmentioning
confidence: 99%
“…Norwegian CMT cases and confirmed that MFN2 gene mutation can also cause intermediate CMT [80] . Of these genes, some are also associated with the classical CMT1 [81] .…”
Section: Plekhg5 and The Ri-cmtc Phenotypementioning
confidence: 62%